COMPARISON OF IN VITRO ACTIVITY OF COLISTIN WITH CEFTOLOZANE/TAZOBACTAM AGAINST MULTI DRUG RESISTANT PSEUDOMONAS AERUGINOSA “A LAST LINE TREATMENT AGAINST MDR” - Islam, K. M. Anwarul; Khan, Muhammad Aitmaud Uddolah; Azhar, Sarah; Ahmed, Muhammad Rashid; Khurram, Sumreen; Masood, Hina; Farooq, Lubna (American International Journal of Multidisciplinary Scientific Research, 2020)
ObjectivesTo evaluate and compare in vitro activity of Ceftolazane / Tazobactum and Colistin against Multi Drug Resistant (MDR) strains of Pseudomonas aeruginosa.MethodologyAfter ethical approval this in vitro cross-sectional study was conducted from October 2017 to April 2018. Routine samples of pus, wound swabs, blood, tracheal aspirates and urine were collected and received from the in-patient and out-patient clinics. All the samples were submitted for culture and sensitivity testing at the microbiology laboratory of Ziauddin University Hospital, North Nazimabad campus. All the samples were processed according to the provided microbiological procedures, CLSI Guidelines 2018. ResultsForty sample from the out-patient clinics represented pre-dominance of Multi Drug Resistant strains of Pseudomonas aeruginosa (which was found to be 41.2%). On culture and sensitivity testing, it was observed that 60% of the MDR strains of P. aeruginosa were susceptible to Ceftolazane / Tazobactum which was markedly comparable to the susceptibility shown by Colistin (99%).Statistically, P value was highly significant and was found to be 0.0001.ConclusionColistin showed superior activity as compared to Ceftolazane / Tazobactum against MDR isolates of P. aeruginosa. Thus, Colistin has proven to be a possible and important alternative against MDR isolates of P. aeruginosa, but due to its narrow therapeutic window and toxicity profile this drug can be used only when there is no working alternative, or the infection is severely debilitating.